Resilience Evaluation: Validation Of The Subjective Resilience Questionnaire For Adults (SSRQA): Indonesian Version - Kholis, Anja Hesnia; Hidayah, Nurul; Priyanti, Ratna Puji; Elina, Agusta Dian; Kurdi, Fahruddin (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The aim of this study is to translate, adapt, and validate the SSRQA into Indonesian. Methods: Construct validity was assessed by 5 experts in the fields of disaster nursing, mental health, and community nursing. Results: The S-CVI result was 0.9575. Construct validity was tested using PCA (Principal Component Analysis) with N = 200. Reliability was assessed using Cronbach's alpha. The eigenvalue and explanation percentage results showed 18.5%, indicating that the eigenvalue of factors in the SSRQA was sufficient. Cronbach's alpha was obtained as 0.923. Conclusion: The Indonesian version of SSRQA has been validated and can be used to assess resilience based on the perceptions of the Indonesian community